Does Innovation impact the Financial Performance of High-Tech Firms during Different Life Cycle Stages? Evidence from S&P500 Firms - Ramzan, Muhammad; Lau, Wee-Yeap; Bawazir, Abdullah Abdulaziz; Belhaj, Fozi Ali (International Journal of Economics and Financial Issues, 2025)
There has been some resurgence of interest in high-tech firms like Google, Amazon, Facebook, and Apple in the era of IoT. The study extends the literature by examining the impact of innovation on firm performance of high-tech firms in the context of firm life cycle stages. Based on the patents and R&D data of 149 high-tech firms from four sectors like communication services, information technology, healthcare and consumer discretionary from 2002 to 2019, our results show that: First, Innovation has a significant relationship with firm performance. Second, patents have a significant and positive relationship with firm performance. Third, R&D is negatively related to firm performance as it is seen as an expenditure. Fourth, the impact of Innovation on firm performance is strongly observed in the decline stage. Fifth, the firm life cycle enhances the impact of Innovation on financial performance more in the information technology and healthcare sectors. Overall, the fixed-effect model is preferred across all estimations, and firm size and age explain firm performance. Our findings provide some stylised facts of high-tech firms on Innovation and firm performance over their life cycle.